THE IMPORTANCE OF HUMAN CAPITAL INVESTMENTS IN THE INNOVATION ECONOMY (American Journal of Business Management, Economics and Banking, 2025)
The article discusses the essence of investing in human capital and examines the impact of these investments on the development of the country in the context of the innovative economy. The main directions of investment in human capital are also analyzed. At the end of the work, conclusions and recommendations on the topic were formed.